'Britain needed aeroplanes': First World War Flax-Growing at Podington, Bedfordshire (UK). (3rd July 2018) - Stamper, Paul
ABSTRACT: Linen is made from flax. Before 1914 the crop had largely fallen out of cultivation in England, but especially in the latter part of the First World War, it became essential for Britain to greatly increase the amount it grew as imports of it largely stopped. The military's demands for linen-based products such as tents and webbing were already almost insatiable, and as the size of the air fleet, and aircraft themselves, continued to grow, there was a specific requirement for high-quality 'aircraft cloth' to cover wings and airframes. This article describes wartime flax cultivation, especially on the Bedfordshire–Northamptonshire border. Much of the crop was gathered by prisoners of war and college girls, activity recorded in paintings by Randolph Schwabe, an official war artist.